Clinical profile of ossicles in chronic suppurative otitis media: a study of 100 cases - Bangera, Divya R.; Kulkarni, Shreeya V.; Dhawale, Anuradha S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: To assess the status of ossicular chain intraoperatively in patients with chronic suppurative otitis media. Methods: This was an observational study carried out in the department of ENT for a period of two years. About 100 patients of CSOM both safe and unsafe type was included in the study. They were then posted for appropriate surgery and their intraoperative ossicular findings were recorded. Results: Out of 100 cases, malleus was found intact in 80 cases, eroded in 17 cases and absent in 3 cases. Incus was the ossicle most commonly found eroded in the study. It was intact in 65 cases, eroded in 29 cases and absent in 6 cases. The most commonly necrosed part was the long process of incus found in 25 cases. Stapes was found to be intact in 77 cases and suprastructure of stapes was eroded in 23 cases. Conclusions: We found malleus to be the most resistant ossicle to erosion in CSOM, whereas incus was found to be the most susceptible. The incidence of ossicular erosion was much greater in unsafe CSOM than in safe CSOM.